Faktor-faktor yang Mempengaruhi Konsumen untuk Berbelanja di Supermarket Carrefour Yogyakarta - Singgih Santoso (Jurnal Riset Manajemen dan Bisnis, 2007)
The growing of modern market such as minimarket, supermarket and hypermarket, has an impact on Indonesian customer shopping behavior. Traditionally, many customers visit traditional market for daily needs purchasing. However, recently customers have switched their visit -from traditional to modern retail market. The aim of this research is to examinewhat factors affict customer to visit and spend their monE) in supennarket.The result shows tliat there are two significant factors that generate the switching behavior. Firstly, the factor called Hedonic Yalue, which ,s *"orurid by store layout, lighting, music, location, information technology supporting anC human resources capabilities. Secondly, the factor calledUtilitarian Value, measured by product completeness, product layout, store image and price competitiveness.